A dual-stage low-power converter driving for piezoelectric actuator applied in micro robot. (4th February 2019) - Mu, Ye; Hu, Tianli; Gong, He; Wang, Lijun; Li, Shijun
In this article, a dual-stage converter driving for a piezoelectric actuator based on flyback circuit was designed and implemented, which could be applied in a micro robot. A low-voltage direct current could be converted to a high-voltage alternating current through flyback circuit and direct current/alternating current circuit in low-power condition. In the direct current/direct current stage, the charging and discharging process was realized to generate a high voltage bias from a low voltage directly supplied by battery. Then, the high voltage was converted into alternating waveform by an energy recovery circuit in direct current/alternating current stage. Experiments were conducted to verify the ability of the proposed converter to drive a 100-V-input piezoelectric bimorph actuator using a prototype 108 mg (excluding printed circuit board mass), 169 (13 × 13) mm 2, and 500-mW converter. According to the experimental results, this converter could be used for driving piezoelectric actuator applied in micro robot.